2008 IEEE International Conference on Software Maintenance 2008
DOI: 10.1109/icsm.2008.4658056
|View full text |Cite
|
Sign up to set email alerts
|

Improving maintenance in AOP through an interaction specification framework

Abstract: The invasiveness of aspects is beneficial to modularize crosscutting concerns that require the modification of the data or control flow. However, it introduces subtle errors that are hard to locate and fix in case of evolution. In this paper we illustrate this issue by evolving a program implemented using aspects. Interaction issues, between aspects and the program, emerge from this evolution. We locate them through manual inspection and test execution. This tedious process motivates the need for an abstract s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…Thus, it seems that the abstractions that AOP has provided to solve some of the evolution problems with traditional software, actually introduce a series of new evolution problems. This phenomenon has been called the evolution paradox of AOP [39], [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it seems that the abstractions that AOP has provided to solve some of the evolution problems with traditional software, actually introduce a series of new evolution problems. This phenomenon has been called the evolution paradox of AOP [39], [28].…”
Section: Discussionmentioning
confidence: 99%
“…Munoz et al [28] showed that aspects offer efficient mechanisms to implement crosscutting concerns, but that aspects can also introduce complex errors in case of evolution. To illustrate these issues, they implemented and then evolved a chat application.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, the quantification and obliviousness properties of AO languages, which are the very advantage offered by AOP, turned out to be a source of difficulties for reasoning about the behavior of AO programs (Griswold et al 2006;Munoz et al 2008). Since aspects can modify data structures or control flow in non-local places, they undermine a programmer's ability to reason locally about the behavior of the module (Dantas and Walker 2006).…”
Section: Motivationsmentioning
confidence: 99%
“…The resulting feature code was hard to understand and maintain due to strong and implicit coupling and fragile pointcuts. Munoz et al (2008) showed that aspects offer efficient mechanisms to implement crosscutting concerns, but that aspects can also introduce complex errors in case of evolution. To illustrate these issues, they implemented and then evolved a chat application.…”
Section: Other Studiesmentioning
confidence: 99%
See 1 more Smart Citation